2014
DOI: 10.19126/suje.46033
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlerin Mesleki Profesyonelliği İle İş Doyumları Arasındaki İlişki

Abstract: ÖzBu çalışmanın amacı, öğretmenlerin mesleki profesyonelliği ile iş doyumları arasındaki ilişkiyi belirlemektir. Tarama modelindeki araştırmanın örneklemi Kütahya il merkezindeki okullarda görev yapan 363 öğ-retmenden oluşmaktadır. Veriler, Öğretmenlerin Mesleki Profesyonelliği Ölçeği ve İş Doyumu Ölçeği ile toplanmıştır. Öğretmenlerin Mesleki Profesyonelliği Ölçeği, Kişisel Gelişim, Kuruma Katkı, Mesleki Duyarlılık ve Duygusal Emek olmak üzere dört faktörden oluşmaktadır. Verilerin analizinde betimsel istatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 13 publications
3
31
0
17
Order By: Relevance
“…These behaviours of teachers are also positively related to the quality of instructional practices (Cohen & Hill, 2000), classroom management strategies (Guskey, 1986), improving student learning (Hoque, Alam, & Abdullah, 2011;McDonald, Son, Hindman & Morrison, 2005;Poekert, 2012), school development (Cansoy & Parlar, 2016), teacher job satisfaction (Altınkurt & Yılmaz, 2014), confidence in colleagues (Dean, 2011), teacher self-efficacy and confidence in the school principal (Koşar, 2015). Teacher professionalism refers to enhancing the standards towards student learning and the quality of practices in improving instruction (Hargreaves, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours of teachers are also positively related to the quality of instructional practices (Cohen & Hill, 2000), classroom management strategies (Guskey, 1986), improving student learning (Hoque, Alam, & Abdullah, 2011;McDonald, Son, Hindman & Morrison, 2005;Poekert, 2012), school development (Cansoy & Parlar, 2016), teacher job satisfaction (Altınkurt & Yılmaz, 2014), confidence in colleagues (Dean, 2011), teacher self-efficacy and confidence in the school principal (Koşar, 2015). Teacher professionalism refers to enhancing the standards towards student learning and the quality of practices in improving instruction (Hargreaves, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Weil (1997), Shann (1998) In terms of their seniority, there was no significant difference in the job satisfaction level of teachers. Altınkurt and Yılmaz (2014), similarly indicated that, seniority did not cause any significant difference in the job satisfaction of their participants. On the contrary, Güner (2007) and Şen (2008) reported that job satisfaction increases in parallel with seniority years.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 69%
“…On the contrary, low job satisfaction leads to alienation to the job, meaninglessness of the job for themselves, aggressive reactions, resistance to change, and similar negative consequences (Altınkurt and Yılmaz, 2014). Teacher job satisfaction has an important function in the increasement of the quality in education.…”
Section: Teacher Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study carried out by Kalay, Arslan and Oflas (2013) in which job satisfaction of nonphysician allied health personnel was examined, it was determined that job satisfaction is low. In various studies conducted in different government institutions, it was determined that job satisfaction levels are at medium level (Günbayı, 2000;Koç, Yazıcıoğlu & Hatipoğlu, 2009;Yılmaz, 2012;Altınkurt & Yılmaz, 2014). At levels of job satisfaction according to gender, significant difference between job satisfaction points and internal and external job satisfactions which are sub-dimensions wasn't found.…”
Section: Discussionmentioning
confidence: 99%